Digital Branding of the Kutai Kartanegara Tourism Office on @Visitingkutaikartanegara Instagram Account in Increasing Tourist Visits - Hagi Nur Fadilla; Johantan Alfando WS; Kadek Dristiana Dwivayani; Harry Isra Muhammad (Publikasi Indonesia, 2024)
One of the main characteristics in the development of the Industrial Revolution 4.0 is the spread of internet technology. The advantage of the internet lies in its ability to reach audiences without being constrained by geographical restrictions. In this study, the goal is to clarify branding activities in the framework of communication, where its elements, such as branding or branding, are presented through various ways and media, becoming elements of the message in the communication process. The study uses a descriptive approach, as a study that explores events of social action in a natural context, with an emphasis on how individuals understand and interpret their experiences. The result of this study is that the role of Instagram social media can increase the interest of tourists visiting tourist destinations in Kutai Kartanegara Regency, caused by the Kutai Kartanegara Tourism Office which has begun to routinely pay attention to tourism marketing through the role of social media by processing content on @visitingkutaikartanegara Instagram account. In addition, the Instagram account has begun to collaborate with various organizations and influencers to assist the Kutai Kartanegara Tourism Office in carrying out digital branding which can facilitate the dissemination of information through Instagram social media.